2022
DOI: 10.1007/s11356-021-18202-x
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus detection in wastewater and its correlation with human gastroenteritis: a systematic review and meta-analysis

Abstract: Norovirus (NoV) is a major cause of sporadic cases and outbreaks of acute gastroenteritis (AGE), thereby imposing threat to health globally. It is unclear how quantitation of wastewater NoV reflects the incidence of human AGE infections; therefore, we conducted this systematic review and meta-analysis of published NoV wastewater surveillance studies. A literature search was performed, and all studies on NoV wastewater surveillance were identified. Quantitative results were evaluated. The results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 93 publications
5
19
0
Order By: Relevance
“…Correlation between viral loads in wastewater and inpatients were significant for both, IAV and NoV GII, which is in accordance with previous studies [ 9 , 10 , 11 , 12 ]. Inclusion of the GI wastewater signal reduced the correlation coefficient which indicates a difference in hospitalization rates between GII and GI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Correlation between viral loads in wastewater and inpatients were significant for both, IAV and NoV GII, which is in accordance with previous studies [ 9 , 10 , 11 , 12 ]. Inclusion of the GI wastewater signal reduced the correlation coefficient which indicates a difference in hospitalization rates between GII and GI.…”
Section: Discussionsupporting
confidence: 93%
“…Cross-correlation analysis indicated that the wastewater signal coincided with inpatient numbers for IAV und NoV GII. Huang et al (2022) [ 10 ] reported similar results for NoV GII comparing wastewater data with cases and outbreaks of acute gastroenteritis. Kazama et al (2017) [ 9 ] reported similar results for NoV in comparison with clinical cases.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…While metatranscriptomics is able to detect eukaryotic, bacterial, and viral pathogens, several studies have shown that the untargeted methods available are not adequate to detect unknown pathogens with small genomes such as viruses on a large scale at a reasonable cost ( 20 , 24 , 32 , 33 ). Surveillance of viruses in wastewater has been mainly conducted using targeted approaches such as amplicon sequencing for particular pathogen genomes such as SARS-CoV-2 or norovirus ( 4 , 5 , 17 , 20 , 24 , 34 ) or through use of viral concentration methods which remove all bacteria and eukaryotic cells prior to sequencing, thereby removing information on other potential pathogens ( 3 , 35 ). Furthermore, wastewater is comprised of intact as well as cellular debris, and therefore, filtration and concentration methods do not enrich enough for viruses to enable consistent detection by non-targeted sequencing methods ( 20 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…After a confirmed case of polio was detected in New York State in late 2022, wastewater surveillance revealed community transmission of poliovirus in the surrounding counties. 25 Wastewater surveillance has also been used to detect the presence of rotavirus, 26 norovirus, 27 and Mpox. 28…”
Section: Current Use Of Wastewater Surveillance Internationallymentioning
confidence: 99%